Retreats for intramental thinking in collaborative online learning. Issue 1 (2nd January 2017) - Peacock, Susi; Cowan, John
Abstract: Much online learning nowadays depends upon the creation of a generic, quality online educational experience, with a particular emphasis on collaborative conversations. In this discursive piece, drawing upon published scholarship and our facilitation and evaluation of learning in technology-mediated environments, we propose an enrichment to the pedagogy of such approaches, referred to as learner retreats. Such metaphorical spaces recognise the need for a 'quiet, safe place' for the private (internal) reflective thinking of each learner, as a foil to the shared collaborative dialogues in the external world of the online community. This 'headspace', with a specific focus on private thinking, is where community learners may probe and enhance current group thinking through reflection and self-regulatory activities. Guidelines are provided for tutors wishing to optimise the use and impact of such personal retreats, promoting deep individual learning and development within the educational experience of online learning communities.